The Role of Teachers in Developing Children's Responsibility Character in Group B2 At Asisi Onoboi Kindergarten - Fransisca ShellyYunita Asa (Universitas Nusa Cendana, 2022)
Character education is not new in human history. Parents in various ways, since a long time ago before there were formal educational institutions, have tried to educate their children to be good children according to the norms that apply in their culture. The main role of teachers in character education is teachers as educators, teachers, models and role models, motivators, and evaluators. So the researcher took a study on